Pemberian Air Kelapa Muda pada Media Murashige and Skoog (MS) untuk Pertumbuhan Eksplan Nenas Secara In Vitro - Fetmi Silvina; Murniati ' (Jurnal Sagu, 2007)
The aim of this study was to find out concentration of coconut oil which induce growth and development of bud pineapple’s crown. The treatments of this experience consisted of several concentration of coconut oil, such as: K0= without coconut oil, K1= 25% of coconut oil, K2= 50% of coconut oil, K3= 75% of coconut oil. The result shows that treatment without giving coconut oil could accelerate the appearance of bud, producing the highest number of bud and the highest percentage of growth.